Strategi Konselor dalam Pengelolaan Lingkungan Sekolah yang Kondusif di MTs K.H.M Noer Surabaya - Wulan Syafitri; Ali Musthofa; Ari Wahyuni (Program Studi Manajemen Pendidikan Islam UIN Sunan Ampel Surabaya, 2022)
This research focuses on strategies or ways of counselors or BK teachers in creating a conducive school environment. The research problem is that there are many violations in MTS K. H M Noer, so that the counseling teacher or counselor has a way or strategy to discipline students by making rules by working with homeroom teachers and continuously providing responsive services. This study uses a type of qualitative research. The types of data in this study are in the form of narrative sentences and descriptive sentences. Data collection techniques were carried out through documentation and interviews with BK teachers at MTS.K.H.M Noer. By finding data in accordance with the research problem. related to what the counselor's strategy is, what are the methods of responsive service, and how is a conducive school environment. The data analysis starts from data reduction, data presentation, and drawing conclusions regarding the counselor's strategy in creating a conducive school environment.